Dynamic behavior of keyhole and molten pool under different oscillation paths for galvanized steel laser welding. (15th August 2022) - Hao, Yu; Li, Liqun; Sun, Yu; Shao, Chendong; Lu, Fenggui
Highlights: The three dimensional numerical model considering the zinc vapor flow was established. The effect of zinc vapor on molten pool flow was analyzed. The flow behavior under different oscillating paths was simulated. The critical spattering velocity during laser welding was discussed. Abstract: This study investigated the dynamic behavior of a keyhole and molten pool under circular and zig-zag oscillating paths for laser welding on galvanized steel. A large variation in the length of the keyhole and a bulge in the molten pool resulted in more spatters in the case of a circular oscillating path, whereas a little spatter was observed in the case of a zig-zag oscillating path because of the relatively stable keyhole and molten pool observed by a high-speed camera. Numerical simulation results showed that zinc vapor entered the keyhole with a velocity of 93 m/s because of a large amount of zinc evaporation in the first half of the circular oscillating path, leading to a rapid increase in the keyhole size. In this case, the fluid near the rear wall of the keyhole accelerated to 1.7 m/s and gushed out of the molten pool in a spatter. In the zig-zag oscillating path, the zinc vapor continually entered the keyhole at a lower velocity, leading to a relatively stable keyhole. In this case, the maximum liquid velocity of the molten pool was 0.9 m/s, not reached the critical spattering velocity (1.36 m/s), thus no spatter occurred. These numerical results sufficiently explain the dynamic behavior of a keyhole and molten pool induced by zinc vapor, and an effective spatter suppression method is proposed.